2015
DOI: 10.5812/asjsm.24040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resistance Training on Capillary Density Around Slow and Fast Twitch Muscle Fibers in Diabetic and Normal Rats

Abstract: Background:It is well accepted that skeletal muscle conforms to exercise stimulus by increasing capillary density and angiogenesis, but there is less evidence regarding the effect of resistance training on capillary density in flexor hallucis longus (FHL) and soleus muscle.Objectives:In this study, we evaluated the effect of resistance training on capillary density around soleus and FHL muscles in type 1 diabetic rats.Materials and Methods:Thirty-six male rats were divided into four groups: (1) control; (2) di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Increases in the capillary network play important roles in improving aerobic capacity, facilitating oxygen transport, enhancing conductance, and increasing muscle contraction, thus increasing maximal oxygen uptake and physical conditioning. Karimian et al 39 demonstrated that Rt performed by climbing ladders does not change the capillary/fiber ratio in flexor hallucis longus (FHL) or soleus muscles but does increase plasma nitric oxide (NO) concentration, an important factor for regulating and enhancing angiogenesis in diabetic animals.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in the capillary network play important roles in improving aerobic capacity, facilitating oxygen transport, enhancing conductance, and increasing muscle contraction, thus increasing maximal oxygen uptake and physical conditioning. Karimian et al 39 demonstrated that Rt performed by climbing ladders does not change the capillary/fiber ratio in flexor hallucis longus (FHL) or soleus muscles but does increase plasma nitric oxide (NO) concentration, an important factor for regulating and enhancing angiogenesis in diabetic animals.…”
Section: Discussionmentioning
confidence: 99%
“…The resistance training protocol was adapted from a previous study [ 28 ]. Rats in the exercise-trained group (DM + EXE) were trained to climb a 135-cm ladder (85 °C incline) with weight secured to their tails.…”
Section: Methodsmentioning
confidence: 99%
“…In concert with the findings described above, Mota et al, 62 showed the effectiveness of RT to treat endothelial dysfunction and prevent an increase in arterial BP in type 1 diabetic rats. Karimian et al 63 showed increased plasma angiogenic factors such as NO in diabetic rats after RT.…”
Section: Cardiac Functionmentioning
confidence: 99%